SC37 In-situ Simulation-Based Team Training in Transcathter Aortic Valve Implantation (TAVI) emergencies. (3rd November 2019) - Hardman, Gillian; Berrigan, Neil; Liddle, Gillian; Hatch, Mark; Dickinson, Mike; Walker, Antony H
Abstract : Background: Transcatheter Aortic Valve Implantation (TAVI) represents a complex procedure, performed in high risk patients, by a multidisciplinary team (MDT), in the catheter lab. When emergencies occur, they present significant Human Factors challenges. The importance of team training to the recovery of patients following TAVI emergencies is recognised. 1 Following a TAVI emergency, a Serious Incident (SI) was raised. In response, we extended our existing Cardiac Surgery in-situ simulation programme to the catheter lab, with the aim of improving team performance, using interprofessional learning, in-situ simulation and deliberate practice with a Human Factors (HF) and non-technical skills (NTS) approach to debriefing. Summary of project: An introduction to the session was followed by a 40-minute simulated scenario of cardiac arrest in a patient at the end of a trans-femoral TAVI procedure. This was performed in-situ in the cardiac catheter lab (figure 1 ). An emergency theatre, perfusion and surgical team were made aware of the session and briefed that they should attend if contacted. Fourteen team members, representative of the MDT, participated in the scenario. The remaining 10 learners observed and actively contributed to the one-hour facilitated debrief. The final 30-minutes of the session was used for deliberate practice of specific emergency steps. Summary of results: A post-session online questionnaire using a 5-part Likert scale was used to evaluate the session. The questionnaire was completed by 19 individuals (response rate 79%). Results of the questionnaire are outlined in Table 1 . All participants expressed a desire for further simulation-based education sessions. Practice development areas identified during the debriefing were escalated to the management teams and quality improvement plans have been implemented. Discussion: In-situ simulation-based team training is now well established within our Cardiothoracic team at the Lancashire Cardiac Centre, with monthly in-situ team training. An SI has prompted us to extend this education approach and successfully adapt it to a related working environment, providing real-time identification of practice development areas, fostering improved team working across disciplines and improving departmental patient safety culture. Conclusions and recommendations: Further work is required to assess the impact of this session on behaviour, patient safety and outcomes following emergency complications after TAVI. We recommend in-situ simulation for the investigation and resolution of SI's occurring in complex working environments. We continue to develop regular, in-situ simulation-based team training, with a focus on Human Factors and Non-technical skills, to embed this approach within the learning culture of our department. References: Tam DY, Jones PM, Kiaii B, Diamantouros P, Teefy P, Bainbridge D, Cleland A, Fernanded P, Chu M. Salvaging catastrophe in Transcatheter Aortic Valve Implantations: rehearsal, preassigned roles, and emergency preparedness. Can J Anesth 2015;62:918–926